Control of Anthracnose and Gray Mold in Pepper Plants Using Culture Extract of White-Rot Fungus and Active Compound Schizostatin. Issue 1 (2nd January 2019) - Dutta, Swarnalee; Woo, E-Eum; Yu, Sang-Mi; Nagendran, Rajalingam; Yun, Bong-Sik; Lee, Yong Hoon
Abstract: Fungi produce various secondary metabolites that have beneficial and harmful effects on other organisms. Those bioactive metabolites have been explored as potential medicinal and antimicrobial resources. However, the activities of the culture filtrate (CF) and metabolites of white-rot fungus ( Schizophyllum commune ) have been underexplored. In this study, we assayed the antimicrobial activities of CF obtained from white-rot fungus against various plant pathogens and evaluated its efficacy for controlling anthracnose and gray mold in pepper plants. The CF inhibited the mycelial growth of various fungal plant pathogens, but not of bacterial pathogens. Diluted concentrations of CF significantly suppressed the severity of anthracnose and gray mold in pepper fruits. Furthermore, the incidence of anthracnose in field conditions was reduced by treatment with a 12.5% dilution of CF. The active compound responsible for the antifungal and disease control activity was identified and verified as schizostatin. Our results indicate that the CF of white-rot fungus can be used as an eco-friendly natural product against fungal plant pathogens. Moreover, the compound, schizostatin could be used as a biochemical resource or precursor for development as a pesticide. To the best of our knowledge, this is the first report on the control of plant diseases using CF and active compound from white-rot fungus. We discussed the controversial antagonistic activity of schizostatin and believe that the CF of white-rot fungus or its active compound, schizostatin, could be used as a biochemical pesticide against fungal diseases such as anthracnose and gray mold in many vegetables.